On the Killing form of Lie Algebras in Symmetric Ribbon Categories - Buchberger, I.; Fuchs, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
As a step towards the structure theory of Lie algebras in symmetric monoidal categories we establish results involving the Killing form. The proper categorical setting for discussing these issues are symmetric ribbon categories.